1988
DOI: 10.1016/s0022-5347(17)41599-0
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Bladder Rupture after Augmentation Enterocystoplasty

Abstract: Delayed bladder perforation with peritonitis following augmentation enterocystoplasty in children with spina bifida is a serious and potentially life-threatening complication. Our experience with 4 such cases is presented. All patients had spina bifida with a neuropathic bladder and they had undergone augmentation enterocystoplasty with a tubular colonic segment of large bowel as part of an undiversion procedure. All patients were being managed with intermittent self-catheterization. The interval from augmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…Mucus provides a protective layer to the bowel epithelium in its natural environment, and an intact layer of mucus may be important in protecting the bowel patch from contact with urinary carcinogens and other substances [112]. However, mucus accumulation can predispose to UTI, stone formation and BOO, and can occasionally contribute to bladder perforation, especially in patients with neuropathy [113,114]. Oral ranitidine can reduce the amount of mucus produced [115] and acetylcysteine washouts help to dissolve excess mucus [116].…”
Section: Mucusmentioning
confidence: 99%
“…Mucus provides a protective layer to the bowel epithelium in its natural environment, and an intact layer of mucus may be important in protecting the bowel patch from contact with urinary carcinogens and other substances [112]. However, mucus accumulation can predispose to UTI, stone formation and BOO, and can occasionally contribute to bladder perforation, especially in patients with neuropathy [113,114]. Oral ranitidine can reduce the amount of mucus produced [115] and acetylcysteine washouts help to dissolve excess mucus [116].…”
Section: Mucusmentioning
confidence: 99%
“…Reported rates of bladder perforation following augmentation range between 6-13% (9,22,(46)(47)(48)(49). Perforation occurs due to increased intravesical pressure, which may result from chronic bladder over-distention, chronic infection, traumatic catheterization, and ischemic necrosis of the intestinal segment used for the augmentation (50)(51)(52)(53)(54)(55)(56). Bladder perforation usually demands exploratory laparotomy with externalization of VPS (if present), to reduce the risk of CNS infections.…”
Section: Perforationmentioning
confidence: 99%
“…The most important and a potentially lethal complication is bladder perforation. [5][6][7][8] The etiology of bladder perforation is not exactly known. However, some authors have suggested that it is related to ischemic changes at the ileal-anastomotic line.…”
Section: Analysis Of Anastomotic Line Perfusion With Fluorescent Molementioning
confidence: 99%